Arteriovenous fistula of the pulmonary circulation: Relationship with Rendu - Osler - Weber disease. Regarding 14 observations - Muras, Olga; Torres, Jorge E.; Praderi, Luis A. (Cirugía del Uruguay, 1979)
The arteriovenous fistula in lung is a rare condition. The paper contains a review of main clinical characteristics, radiological examinations and other tests which render diagnosis easy, performed on a series of 14 patients. The authors then proceed to analyze its connection with Rendu - Osler - Weber disease, considering the condition herein described as one of its manifestations. Finally, on the basis of studies performed, the authors sustain that the latter is a systemic vascular displasia.